CAPE GOOSEBERRY (Physalis peruviana L.) MINIMALLY - RESTREPO, Ana Maria; CORTÉS R., Misael; MÁRQUES, Carlos J. (Vitae, 2009)
Modern consumers are interested in healthy food to ensure healthy ageing, with the aim of ensuring a healthy ageing. Research expects industry level achievement for fortified fruit as an alternative. This study assesses the useful life time cape gooseberry (Physalis peruviana L.) fortified with vitamin E using the technique of vacuum impregnation (IV), depending on the colour, texture and stability of vitamin E at different storage conditions. The active components of vitamin E are quantified by HPLC and levels in the fruit are reported based on 100 grams fresh capegooseberry. The answer to the IV is affected by the area and the distribution of the pores of the apex, which contributed to obtain levels of fortification in the final product exceeding the criteria set (100% of the Consumer Daily Recommendation (RDC) Colombia): 159,8 ± 38,0% RDC ≅ 35,15 ± 8,35 mg dl-α-tocopherol acetate with a time of useful life of 15 days. The process IV and vacuum packaging were significant in color (darker) and the texture (more soft).